Widefield Optical Coherence Tomography in Pediatric Retina: A Case Series of Intraoperative Applications Using a Prototype Handheld Device - Nguyen, Thanh-Tin P.; Ni, Shuibin; Liang, Guangru; Khan, Shanjida; Wei, Xiang; Skalet, Alison; Ostmo, Susan; Chiang, Michael F.; Jia, Yali; Huang, David; Jian, Yifan; Campbell, J. Peter (Frontiers in Medicine, 2022)
Optical coherence tomography (OCT) has changed the standard of care for diagnosis and management of macular diseases in adults. Current commercially available OCT systems, including handheld OCT for pediatric use, have a relatively narrow field of view (FOV), which has limited the potential application of OCT to retinal diseases with primarily peripheral pathology, including many of the most common pediatric retinal conditions. More broadly, diagnosis of all types of retinal detachment (exudative, tractional, and rhegmatogenous) may be improved with OCT-based assessment of retinal breaks, identification of proliferative vitreoretinopathy (PVR) membranes, and the pattern of subretinal fluid. Intraocular tumors both benign and malignant often occur outside of the central macula and may be associated with exudation, subretinal and intraretinal fluid, and vitreoretinal traction. The development of wider field OCT systems thus has the potential to improve the diagnosis and management of myriad diseases in both adult and pediatric retina. In this paper, we present a case series of pediatric patients with complex vitreoretinal pathology undergoing examinations under anesthesia (EUA) using a portable widefield (WF) swept-source (SS)-OCT device.